Impact of Oocyte Morphologic Abnormalities on Embryo Development - Damdinsuren, Erdenesuvd; Naidansuren, Purevjargal; Choi, Bum Chae; Young, Park Hyo; Gochoo, Mendsaikhan; Baldandorj, Bolorchimeg (Central Asian Journal of Medical Sciences, 2024)
Objectives: This study aimed to investigate the relationship between oocyte morphologic features and embryo development following an Intracytoplasmic Sperm Injection (ICSI) procedure. Methods: In this retrospective study, 485 mature oocytes were obtained from 70 patients undergoing ICSI cycles. Controlled ovarian stimulation was performed using a standard antagonist protocol. Morpho kinetic variables were analyzed using Time-Lapse Monitoring (TLM). The primary outcome measures were fertilization and reasonable embryo rate. Results: The patients’ age ranged from 22 to 45 years (34.9±4.9 on average). From all retrieved MII oocytes, 285 (59.0%) showed at least one morphologic aberration. The organelle cluster and ovoid shape were related to a lower fertilization rate (OR: 0.35 p-value 0,045 and OR:0.137; p-value 0,048, respectively). Time to 5 cells (t5) and time to 7 cells (t7) were different between normal and abnormal morphologic oocytes (P-value 0.016 and 0.017, respectively). Average Oocyte Quality Index (AOQI) negatively correlated with the number of good embryos. Conclusions: In our study, the fertilization potential of organelle clusters and ovoid-shaped oocytes was lower. The t5 and t7 were significantly longer in the abnormal oocyte group.